Comparative Analysis Of 4G LTE Network Quality At 900 Mhz And 2100 Mhz Frequencies - Ditto Putra; Afrizal Yuhanef; Dikky Chandra (International Journal of Wireless And Multimedia Communications, 2024)
4G networks were created to provide excellent service and fast data transmission. The goal is to promote better reception, maintain smooth data flow, and speed up information exchange. Indonesia has six mobile operators, each of which has the right to use the radio frequency spectrum to deploy mobile network services. The radio frequencies used are divided into 450 MHz, 850 MHz, 900 MHz, 1,800 MHz, 2,100 MHz, and 2,300 MHz. This research focuses on the comparison of 4G LTE network quality at 900 MHz and 2100 MHz frequencies. Data collection is done by conducting a drive test and using the dedicated mode method. The software that is utilized for data processing are TEMS Pocket and TEMS Discovery Device. The network quality of both frequencies is measured based on RSRP, SINR, and Throughput parameters. The results of network quality measurements were obtained for the 900 MHz frequency, namely, RSRP worth 79.54%, SINR worth 65.69%, and Throughput worth 37.65%. While the frequency of 2100 MHz, namely, RSRP is worth 82.1%, SINR is worth 76.84%, and Throughput is worth 72.18%. Of the two frequencies, the 2100 MHz frequency has a better value than the 900 MHz frequency.